PERAN PENTING KEPEMIMPINAN TRANSFORMASIONAL DALAM PROSES PENGEMBANGAN MADRASAH - Buchori, Uuh; Ma'mur, Ilzamudin; Muhtarom, Ali (STAI Ma'had Aly Al-Hikam Malang, 2024)
Transformational leadership plays a crucial role in the development of madrasahs as Islamic educational institutions. This qualitative research aims to understand the significance of transformational leadership in madrasah development. Through a qualitative approach, this study explores relevant journals to gain a deeper understanding of the role of transformational leadership in madrasah development. The findings of this study indicate that transformational leadership significantly contributes to madrasah development. Transformational leaders have the ability to inspire, empower, and create a supportive work climate that fosters change and innovation in the context of education and teaching. Transformational leadership also facilitates constructive assessment and feedback, as well as continuous development of teacher competencies. It is crucial for madrasah leaders to develop effective transformational leadership skills. By doing so, madrasah leaders can create an inspirational, empowering, and motivating learning environment for teachers and students. This contributes to the overall development of madrasahs, including enhancing the quality of education, addressing challenges and issues, and improving teacher performance and student motivation.